SGLT-2 inhibitors and nephroprotection: a systematic review and meta-analysis - Alda João Araujo Andrade (2020)
Introduction: Diabetic nephropathy persists an extremely prevalent microvascular complication in individuals with Type 2 Diabetes Mellitus. Some studies reported a reduction in albuminuria and preservation of estimated Glomerular Filtration Rate as a class-effect of SGLT2 inhibitors. However, some uncertainty remains. Therefore, we aimed to systematically review the association between the use of SGLT2 inhibitors and the impact on renal outcomes in Type 2 Diabetes Mellitus patients. Methods: We performed a systematic review and meta-analysis of randomized controlled trials of SGLT-2 inhibitors that assessed glomerular filtration rate and urinary albumin-to-creatinine ratio in patients with type 2 diabetes. We searched Web of Science, Scopus and MEDLINE from database inception to September, 2019. We performed random-effects meta-analysis assessing the association between SGLT-2 inhibitors use and estimated glomerular filtration rate and urinary albumin-to-creatinine ratio. Results: Thirty-six studies were included in this meta-analysis. Canagliflozin significantly contributed to preserve the mean estimated glomerular filtration rate (+1.20 mL/min per 1,73m2; 95% CI: 0.91 to 1.48). Empagliflozin significantly decreased urinary albumin-to-creatinine ratio by -44.40mg/g (95% CI: -80.47 to -8.34). Concerning SGLT-2 inhibitors overall, there was a significant preservation of estimated glomerular filtration rate (0.54 mL/min per 1,73m2; 95% CI: 0.38 to 0.71) and urinary albumin-to-creatinine ratio reduction (-11.11mg/g; 95% CI: -19.62 to -2.61). No statistically significant association was found between the other subgroups and the studied outcomes. Conclusions: SGLT-2 inhibitors are associated with a delay in decreasing of estimated glomerular filtration rate and with a decrease in urinary albumin-to-creatinine ratio.